ROLE OF RAILWAY TRANSPORT IN TOURISM: SELECTED PROBLEMS AND EXAMPLES IN SLOVAKIA - Michniak, Daniel (Quaestiones Geographicae, 2016)
Transport is a very important part of activities in the tourism sector. In addition to the transport of tourists to and within a destination, transport itself can be a tourist attraction. The aim of this paper is to analyse selected problems of railways in Slovakia (a decrease in the importance of railways for passenger transport in Slovakia in the past 20 years, discontinued passenger transport on certain railway tracks and the modernisation of other tracks, and zero-fare public rail transport services for certain categories of passengers), and to present good examples of the use of narrow-gauge railways for the purposes of tourism (the Tatra Electric Railways and the Kysuce-Orava Forest Railway).